Laparoscopic and Robotic Surgery for Endometrial and Cervical Cancer. Issue 9 (September 2021) - Uwins, C.; Patel, H.; Prakash Bhandoria, G.; Butler-Manuel, S.; Tailor, A.; Ellis, P.; Chatterjee, J.
Abstract: Minimally invasive surgery (MIS) has many benefits, in the form of reduced postoperative morbidity, improved recovery and reduced inpatient stay. It is imperative, however, when new techniques are adopted, in the context of treating oncology patients, that the oncological efficacy and safety are established rigorously rather than assumed based on first principles. Here we have attempted to provide a comprehensive review of all the contentious and topical themes surrounding the use of MIS in the treatment of endometrial and cervix cancer following a thorough review of the literature. On the topic of endometrial cancer, we cover the role of laparoscopy in both early and advanced disease, together with the role and unique benefits of robotic surgery. The surgical challenge of patients with a raised body mass index and the frail and elderly are discussed and finally the role of sentinel lymph node assessment. For cervical cancer, the role of MIS for staging and primary treatment is covered, together with the interesting and highly specialist topics of fertility-sparing treatment, ovarian transposition and the live birth rate associated with this. We end with a discussion on the evidence surrounding the role of adjuvant hysterectomy following radical chemoradiation and pelvic exenteration for recurrent cervical cancer. MIS is the standard of care for endometrial cancer. The future of MIS for cervix cancer, however, remains uncertain. Current recommendations, based on the available evidence, are that the open approach should be considered the gold standard for the surgical management of early cervical cancer and that MIS should only be adopted in the context of research. Careful counselling of patients on the current evidence, discussing in detail the risks and benefits to enable them to make an informed choice, remains paramount. Highlights: Minimally invasive surgery is increasingly used in gynaecological oncology. Obesity is prevalent in endometrial cancer and is associated with significant surgical morbidity. Minimally invasive surgery is associated with reduced postoperative complications. Robotic surgery supports increased rates of minimally invasive surgery. The future of minimally invasive surgery for cervix remains uncertain.